Hypertension Prevalence, Awareness, and Control in US Adults Before and After the COVID‐19 Pandemic - Mohammed Essa; Devesh Malik; Yuan Lu; Huanhuan Yang; Erica S. Spatz; Harlan M. Krumholz; Kamil F. Faridi (The Journal of Clinical Hypertension, 2025)
ABSTRACT Hypertension is a leading cause of death and disability in the United States, but national trends in hypertension after the COVID‐19 pandemic remain unknown. We analyzed NHANES data from pre‐pandemic (2017–March 2020) and post‐pandemic (August 2021–August 2023) surveys to determine nationwide prevalence, awareness, and control of hypertension. Weighted, age‐standardized prevalence estimates were compared using Poisson regression with prevalence ratios (PRs). Among 14 449 participants representing 237 million US adults, hypertension prevalence was 49.5% pre‐pandemic versus 47.7% post‐pandemic (PR 0.96; p = 0.15). Overall, hypertension awareness was unchanged (57.7% vs. 53.7%; PR 0.96; p = 0.14) but declined among adults aged 18–39 years (PR 0.78; p = 0.02). Blood pressure control remained low (25.9% vs. 22.3%; PR 0.91; p = 0.06) and worsened in men (PR 0.83; p = 0.01). In conclusion, hypertension prevalence, awareness, and control did not significantly improve post‐pandemic. More aggressive public health efforts are needed to reduce the adverse impacts of hypertension in the United States.